(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2024)
The article examines artist and researcher Pedro Oliveira’s practice for “algorithmic justice”. Through the concept of opacity as defined by Louise Amoore and Édouard Glissant, I will examine Oliveira’s theoretical and artistic production. Oliveira focuses on the German Federal Office for Migration and Refugees’ (BAMF) “accent/dialect recognition software”, a biometric algorithm for identifying the origin of undocumented asylum seekers, known for its discriminatory practices. Through Oliveira’s work, opacity emerges as an aesthetic-political paradigm that suggests new practices for algorithmic justice. Furthermore, opacity is positioned as an episteme able to resist the “regime of recognition” of biometric algorithms. Through works like DESMONTE, Oliveira explores the opacity of listening and its objects, proposing a collective, creative, relational, and embodied practice. His work represents a pioneering intervention in the fields of critical studies on machine listening, voice biometrics, and algorithms, to which this article also aims to contribute.